2022
DOI: 10.3233/npm-210775
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) through infant feeding and early care practices: A systematic review

Abstract: BACKGROUND: Perinatal practices such as breast-feeding, kangaroo mother care, rooming-in, and delayed cord clamping have varied by institution during the COVID-19 pandemic. The goal of this systematic review was to examine the success of different practices in preventing viral transmission between SARS-CoV-2 positive mothers and their infants. METHODS: Electronic searches were performed in the Ovid MEDLINE, Ovid Embase, Cochrane Library, EBSCOhost CINAHL Plus, Web of Science, and Scopus databases. Studies invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…If COVID-19 is suspected or diagnosed, the World Health Organization recommends that mothers and infants could use skin-to-skin contact and other measures (80). However, there was no evidence of vertical transmission from a coronavirusinfected mother (81), and increased virus transmission was not observed in newborns receiving skin-to-skin care (82). As a result, the World Health Organization recommendations for neonatal skin care could be followed (80).…”
Section: Discussionmentioning
confidence: 99%
“…If COVID-19 is suspected or diagnosed, the World Health Organization recommends that mothers and infants could use skin-to-skin contact and other measures (80). However, there was no evidence of vertical transmission from a coronavirusinfected mother (81), and increased virus transmission was not observed in newborns receiving skin-to-skin care (82). As a result, the World Health Organization recommendations for neonatal skin care could be followed (80).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence summary: One systematic review, 2 guidelines, and 1 observational study were included here 149–152 . One systematic review (28 studies) found no significant difference in COVID‐19 positivity rates in newborns receiving KMC versus controls among mothers with confirmed COVID‐19 152 .…”
Section: Key Questions Recommendations Evidence Overview and Notes On...mentioning
confidence: 99%
“…Evidence summary: One systematic review, 2 guidelines, and 1 observational study were included here 149–152 . One systematic review (28 studies) found no significant difference in COVID‐19 positivity rates in newborns receiving KMC versus controls among mothers with confirmed COVID‐19 152 . The observational study found that the survival benefit of KMC far outweighed the small risk of COVID‐19 death in preterm and LBWIs, especially in low‐ and middle‐income countries 151 .…”
Section: Key Questions Recommendations Evidence Overview and Notes On...mentioning
confidence: 99%
“…If mother–baby separation is unavoidable due to poor mother’s health condition, newborn should be fed with pumped breast milk or pasteurized donor breast milk until breastfeeding can be resumed [ 96 ]. Another recent systematic review showed increased positivity rates of SARS-CoV-2 among newborns who were breastfed and roomed-in (almost all remained asymptomatic), but there were no differences in SARS-CoV-2 positivity rates in neonates who received skin to skin care or delayed cord clamping [ 97 ]. A recent Italian study confirmed that vertical and perinatal SARS-CoV-2 infection is rare, and breastfeeding does not increase the risk of COVID-19 [ 98 ].…”
Section: Breastfeeding and Infectionsmentioning
confidence: 99%